SIFAT MEKANIK DAN CACAT PENYUSUTAN (SHRINKAGE) AKIBAT VARIASI KOMPOSISI CAMPURAN DAUR ULANG POLYETHYLENE PADA INJECTION MOULDING - Muhammad Ghilman Badri; Mahros Darsin; Dedi Dwilaksana (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2014)
Injection moulding is one process to form plastic by compress the melted plastic in a closed die. The raw material for the process either pure plastic pellet or mixed with recycled plastics. this research focused on finding the acceptable percentage of recycled the raw material in term of tensile strengh and shrinkage. The composition is varied from 0% to 100% of polyethylene. Tensile test shows that the more percentage of recycled the lower is the tensile strenght. on the other hand, the more the recycled composition the highernis shrinkage number. Both decrease of tensile strengh and increase of shrinkage are linearly. Recycled plastic in the raw material makes the composition be not uniform. It leads misrun defect, i.e. the melted plastic solidified before it reach the destined cavity in the mold. Moreover, it also creates more void in the parts. The highest tensile strength of 19.10 N/mm2 when no recycled mixed in, whereas the minimum of 12.05 N/mm2 achieved when 100% recycled was applied. Recycled Composition of 100% also increased by 9,82% compare to pure plastic. Keywords: Recycled plastic, tensile strength, shrinkage.